'Nicky nocky noo', 'Tommy Thumb' - Lynda; Awre, Gabrielle (The University of Hull, 2017)
A conversation around children's 'finger songs' and cumulative songs. Lynda knew these from her teaching career. Lynda moved from Derbyshire to Hull at the beginning of her teaching career and had not been long retired when the project took place.